Polymer cross-linked self-curing drug-loaded bone cement and preparation method thereof

By cross-linking polymers, self-curing of drug-loaded bone cement, self-curing of tetracalcium phosphate and hydrogen phosphate to generate hydroxyapatite, and combined with the cross-linking network of polymer biomaterials, the problems of low biological activity and poor mechanical properties of bone cement are solved, faster solidification time and stronger mechanical properties are achieved, and it is suitable for bone defect treatment.

CN119656371AInactive Publication Date: 2025-03-21CENTRAL MEDICAL (HUBEI) CO LTD

Patent Information

Application Number
CN202411885550.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing bone cement has low biological activity, poor mechanical properties, long solidification time and inability to form interconnected porous structures in situ, limiting its application in bone defect treatment.

Method used

The polymer cross-linked self-curing medicated bone cement is used to self-cure tetracalcium phosphate and calcium hydrogen phosphate to generate hydroxyapatite, combined with the cross-linking network of polymer biomaterials, shorten the solidification time, enhance mechanical strength, and avoid thermal effects during forming.

Benefits of technology

It improves the biological activity and mechanical properties of bone cement, shortens the solidification time, enhances the ability of cell attachment and osteogenesis and differentiation, and avoids thermal damage and drug activity destruction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656371A_ABST
    Figure CN119656371A_ABST
Patent Text Reader

Abstract

The invention relates to macromolecular cross-linked self-curing drug-loaded bone cement and a preparation method thereof, and belongs to the technical field of bone repair biological materials. The preparation method comprises the following steps: grinding the purchased tetracalcium phosphate and calcium hydrophosphate, and sieving through a screen to obtain powder with different granularities; uniformly mixing tetracalcium phosphate, calcium hydrophosphate, a cross-linking agent and medicines to obtain bone cement powder; dissolving a polymer biological material in purified water to obtain a polymer biological material aqueous solution; uniformly mixing the bone cement powder and the polymer biological material aqueous solution, and naturally curing at 37 DEG C; hydroxyapatite generated during self-curing of tetracalcium phosphate and calcium hydrophosphate has good biological activity, released calcium and phosphate ions are beneficial to formation of a bone-like apatite layer, and bone inductivity is improved. The cross-linking of the polymer biological material can provide a three-dimensional interconnected network for the bone cement, and is beneficial to drug loading, cell attachment, ingrowth and subsequent osteogenic differentiation and vascular remodeling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of bone repair biomaterials, and in particular is a drug-loaded bone cement combining cross-linked polymer biomaterials with calcium phosphate self-solidification and a preparation method thereof. Background Art

[0002] Bone defect refers to the shortage of bone caused by trauma, disease or surgery. The main method of treating bone defects is bone filling surgery. In bone filling surgery, the repair material used for bone filling is crucial. The ideal bone filling material should have the following characteristics: (1) good biocompatibility and no immune rejection reaction; (2) sufficient mechanical properties to provide support for the defect site; (3) good bone inductivity to promote the formation of new bone and accelerate healing; (4) controllable degradation performance to provide space for new bone regeneration; (5) sufficient source and low price.

[0003] Self-setting calcium phosphate bone cement is a bone filling material that can harden and form itself at room temperature. It is mainly composed of calcium phosphate powder and water. After the two are mixed, other calcium phosphates will spontaneously transform into hydroxyapatite due to the lowest solubility of hydroxyapatite in water, and finally harden and form hydroxyapatite. Hydroxyapatite is the main inorganic component of human bone and has good biological activity. The material does not release heat significantly during use and is easy to operate. However, it also has limitations, such as poor initial mechanical properties, long solidification time (30-60 minutes), and the inability to form an interconnected porous structure in situ to promote cell attachment, ingrowth, and subsequent osteogenic differentiation and vascular remodeling.

[0004] The cross-linked network of polymer biomaterials is a three-dimensional mesh structure formed by polymer chains through cross-linking reactions. This cross-linking allows the polymer solution to quickly transform from a liquid to a hydrogel, giving the polymer material higher mechanical properties and adjustable degradation properties, and the interconnected macropores formed by the three-dimensional network are more conducive to cell migration and nutrient penetration. Therefore, the cross-linked network of polymer biomaterials is widely used in fields such as tissue regeneration engineering and drug delivery systems.

[0005] Drugs play an auxiliary role in the treatment of bone defects, mainly used to relieve symptoms, promote bone regeneration and prevent infection. Drugs that relieve symptoms, such as ibuprofen and loxoprofen sodium, can relieve pain caused by bone defects; drugs that promote bone regeneration, such as bone morphological protein and naringin, can stimulate new bone formation; antibiotics that prevent infection can control bacterial infection and avoid further aggravation of bone defects. Summary of the invention

[0006] The purpose of the present application is to provide a polymer cross-linked self-curing drug-loaded bone cement and a preparation method thereof, so as to solve the problems of low biological activity and poor mechanical properties of current bone cement.

[0007] On one hand, the present invention provides a polymer cross-linked self-curing drug-loaded bone cement, wherein the bone cement raw materials include tetracalcium phosphate and calcium hydrogen phosphate, a cross-linking agent, a drug, and a polymer biomaterial.

[0008] Optionally, the cross-linking agent is genipin or 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS).

[0009] Optionally, the drug is ibuprofen sodium or naringin or penicillin sodium.

[0010] Optionally, the polymer biomaterial is collagen or gelatin or chitosan or carboxymethyl chitosan.

[0011] Another aspect of the present invention provides a method for preparing a polymer cross-linked self-curing drug-loaded bone cement, the method comprising:

[0012] (1) grinding the purchased tetracalcium phosphate and calcium hydrogen phosphate, and passing through a sieve after grinding to obtain powders of different particle sizes;

[0013] (2) mixing tetracalcium phosphate, calcium hydrogen phosphate, a cross-linking agent, and a drug uniformly to obtain bone cement powder;

[0014] (3) dissolving the polymer biomaterial in purified water to obtain a polymer biomaterial aqueous solution;

[0015] (4) Mix the bone cement powder and liquid evenly and allow them to solidify naturally at 37°C.

[0016] Preferably, after grinding, the powder is passed through a sieve of 200, 400, 600, 800, or 1000 mesh to obtain powders with particle sizes of 38-75 μm, 23-38 μm, 18-23 μm, or 13-18 μm.

[0017] Preferably, the bone cement powder comprises, by weight, 0.73 parts of tetracalcium phosphate, 0.27 parts of calcium hydrogen phosphate, 0.002-0.01 parts of a cross-linking agent, and 0.001-0.005 parts of a drug.

[0018] Preferably, the concentration of the polymer biomaterial aqueous solution is 3-10%.

[0019] Preferably, the ratio of bone cement powder to polymer biomaterial aqueous solution is 0.1-1 g / mL.

[0020] The present invention has the following technical effects or advantages:

[0021] (1) The hydroxyapatite generated during the self-solidification of tetracalcium phosphate and calcium hydrogen phosphate has good biological activity. The released calcium and phosphate ions are conducive to the formation of a bone-like apatite layer and improve bone inductivity.

[0022] (2) The cross-linking of polymer biomaterials can provide bone cement with a three-dimensional interconnected network, which is conducive to drug loading, cell attachment, ingrowth, and subsequent osteogenic differentiation and vascular remodeling.

[0023] (3) The combination of the self-solidification of tetracalcium phosphate and calcium hydrogen phosphate and the cross-linking of polymer biomaterials shortens the setting time of bone cement and enhances the mechanical strength of bone cement.

[0024] (4) Compared with commonly used acrylic materials, polymer cross-linked self-curing drug-loaded bone cement has no obvious thermal effect during forming, which can prevent the released heat from damaging tissues and destroying the activity of doped drugs.

[0025] (5) The raw materials are widely available, the production process is simple, and it is suitable for mass production.

[0026] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 It is a flow chart of the method provided by the embodiment of the present invention.

[0029] Figure 2 This is a graph showing the curing time of bone cement.

[0030] Figure 3 It is the compressive strength diagram of bone cement.

[0031] Figure 4 It is a graph of the cell activity of bone cement. DETAILED DESCRIPTION

[0032] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.

[0033] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0034] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0035] The technical solution of the embodiment of the present application is to solve the above technical problems, and the overall idea is as follows:

[0036] The applicant discovered during the invention process that current bone cement products are mainly acrylic bone cement and calcium phosphate bone cement. Acrylic bone cement releases a large amount of heat during the solidification stage, which may cause tissue damage, and the particle wear debris generated after implantation may also induce aseptic inflammation; calcium phosphate bone cement has good biological activity, but poor initial mechanical properties, long solidification time (30-60 minutes) and inability to form an interconnected porous structure in situ, which limits its use.

[0037] According to a typical embodiment of the present invention, a polymer cross-linked self-curing drug-loaded bone cement is provided, wherein the raw materials of the bone cement include: tetracalcium phosphate, calcium hydrogen phosphate, a cross-linking agent, a drug, and a polymer biomaterial.

[0038] Hydroxyapatite generated during the self-solidification of tetracalcium phosphate and calcium hydrogen phosphate enhances the biological activity of bone cement; the three-dimensional network structure formed by self-crosslinking of polymer biomaterials is conducive to cell attachment, ingrowth, and subsequent osteogenic differentiation and vascular remodeling; the combination of self-solidification and cross-linking of polymer materials shortens the setting time of bone cement and enhances the mechanical strength of bone cement; polymer cross-linked self-solidifying drug-loaded bone cement has no obvious thermal effect during formation, which can avoid the released heat from damaging tissues and destroying the activity of doped drugs.

[0039] In some embodiments, the particle size of tetracalcium phosphate and dicalcium phosphate is 13-75 μm.

[0040] The solidification of calcium phosphate bone cement is a process of dissolution, reaction, and precipitation. As for the solidification time, the smaller the particle size of the reactants, the faster the dissolution rate and the shorter the precipitation solidification time. As for the mechanical strength, on the one hand, the lower the particle size of the reactants, the more hydroxyapatite is generated, and the higher the mechanical strength after solidification; on the other hand, too low a particle size will cause an increase in the proportion of grain boundaries between the product particles, causing more lattice defects, which is not conducive to the increase of mechanical strength. Therefore, the particle size should be properly controlled to obtain bone cement with higher mechanical strength.

[0041] In some embodiments, the mass fraction of the crosslinking agent in the bone cement powder is 0.002-0.01 parts.

[0042] Crosslinkers transform the microstructure of biomaterials into a three-dimensional network structure, which improves the mechanical properties of bone cement and provides space for cells to attach and proliferate. However, high concentrations of crosslinkers may be cytotoxic and make the crosslinking dense, which is not conducive to osteogenesis and vascular remodeling.

[0043] In some embodiments, the ratio of bone cement powder to liquid is 0.1-1 g / mL.

[0044] On the one hand, the more powder there is, the more hydroxyapatite there is after curing, and the stronger the mechanical strength of the bone cement. On the other hand, the increase in powder content will weaken the cross-linking between polymer biomaterials, which will extend the curing time of bone cement and reduce the mechanical strength.

[0045] The bone cement and preparation method of the present application will be described in detail below in combination with embodiments, control examples and experimental data.

[0046] Example 1

[0047] A method for preparing bone cement, comprising:

[0048] (1) grinding the purchased tetracalcium phosphate and calcium hydrogen phosphate, and passing through 400 and 600 mesh sieves after grinding to obtain a powder with a particle size of 23-38 μm;

[0049] (2) tetracalcium phosphate, calcium hydrogen phosphate, 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC), N-hydroxysuccinimide (NHS), and naringin are uniformly mixed in a ratio of 0.73:0.27:0.01:0.005 by mass to obtain bone cement powder;

[0050] (3) dissolving collagen in purified water to obtain a 5% collagen aqueous solution;

[0051] (4) Mix the bone cement powder and collagen aqueous solution at 1 g / mL and allow to solidify at 37°C.

[0052] Example 2

[0053] A method for preparing bone cement, comprising:

[0054] (1) grinding the purchased tetracalcium phosphate and calcium hydrogen phosphate, and passing through 800 and 1000 mesh sieves to obtain a powder with a particle size of 13-18 μm;

[0055] (2) mixing tetracalcium phosphate, calcium hydrogen phosphate, genipin, and penicillin sodium in a ratio of 0.73:0.27:0.005:0.01 by mass to obtain bone cement powder;

[0056] (3) dissolving carboxymethyl chitosan and collagen (mass ratio 1:4) in purified water to obtain a mixed solution with a concentration of 5%;

[0057] (4) The bone cement powder and the mixed solution were mixed evenly at 0.3 g / mL and allowed to solidify at 37°C.

[0058] Example 3

[0059] A method for preparing bone cement, comprising:

[0060] (1) grinding the purchased tetracalcium phosphate and calcium hydrogen phosphate, and passing through 200 and 400 mesh sieves after grinding to obtain a powder with a particle size of 38-75 μm;

[0061] (2) tetracalcium phosphate, calcium hydrogen phosphate, 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC), N-hydroxysuccinimide (NHS), and sodium ibuprofen are uniformly mixed in a ratio of 0.73:0.27:0.01:0.01 by mass to obtain bone cement powder;

[0062] (3) dissolving gelatin in purified water to obtain a gelatin solution with a concentration of 10%;

[0063] (4) The bone cement powder and the mixed solution were mixed evenly at 0.6 g / mL and allowed to solidify at 37°C.

[0064] The present invention tests the curing time, compressive performance and cell activity of the bone cement in Examples 1-3. The curing time of the bone cement is determined by the Gilmore needle method; the bone cement is made into a regular block solid, and its compressive strength is tested by a universal mechanical testing machine; MC3T3 cells are inoculated on the sample and cultured for three days, and the absorbance values ​​(OD values) of the 1st, 2nd and 3rd are determined by the CCK-8 method. Figure 2 The curing time of bone cement is shown to be within 15 minutes, which meets the requirements of clinical use; Figure 3 The compressive strength of bone cement is shown to be between 0.5-3MPa; Figure 4 The cell activity of bone cement was demonstrated, Example 1 showed cell proliferation activity, and Examples 2 and 3 had no cytotoxicity.

[0065] Comparative Example 1

[0066] A bone cement was prepared according to the method in Example 1 of Chinese Patent CN117122733B.

[0067] Weigh 1.6 g, 0.6 g, 0.2 g and 0.3 g of tricalcium phosphate, calcium sulfate, mineralized collagen and monocalcium phosphate respectively in 90 mL of aqueous solution, add 0.12 g, 0.1 g and 0.1 g of calcium chloride, calcium hydroxide and sodium pyrophosphate respectively to adjust the pH to 5.0 (the ratio of calcium salt substrate to water is 1 g / 30 g), dry at 100 ° C for 2 h and then grind into powder (particle size 0.1 μm) to obtain a bone cement solid phase; take 1.5 g of propylene glycol, add 0.15 ml of acrylate and mix to obtain a bone cement liquid phase; mix at a liquid-to-solid ratio of 0.4 to obtain a bone cement product.

[0068] Comparative Example 2

[0069] A bone repair hydrogel was prepared by referring to the method in Example 1 of Chinese Patent CN114984326B.

[0070] Preparation of a multi-crosslinked injectable bone repair hydrogel: taking corilagin and carboxymethyl chitosan, adding deionized water to wet and mix, grinding until dry and fluffy, and obtaining a corilagin / carboxymethyl chitosan complex; wherein the mass ratio of corilagin to carboxymethyl chitosan is 1:5; dissolving magnesium alginate MA in deionized water, stirring thoroughly, and obtaining a MA solution with a concentration of 0.02 g / mL; adding sodium periodate, stirring and reacting at room temperature and in the dark for 12 hours; then adding ethylene glycol and continuing the reaction for 2 hours to terminate the oxidation reaction; dialyzing with deionized water for 72 hours (dialysis bag cutoff molecular weight: 3500Da), freezing and drying the dialyzed solution at -80°C, and obtaining oxidized magnesium alginate OMA; wherein the mass ratio of MA to sodium periodate is 1:1; the mass volume ratio of MA to ethylene glycol is 1g:5mL; dissolving nanohydroxyapatite in pH 8.5Trils buffer, fully stirred and ultrasonicated for 20 minutes to obtain a solution A with a concentration of 0.2wt%; dopamine hydrochloride was dissolved in deionized water, fully stirred and mixed to obtain a solution B with a concentration of 0.2wt%; then, according to the mass ratio of nanohydroxyapatite to dopamine hydrochloride of 1:1, solution A was added dropwise to solution B at a constant speed and stirred and mixed, the stirring speed was 1000r / min, the stirring was continued for 12h, and freeze-dried to obtain dopamine-coated nanohydroxyapatite PHA; corilagin / carboxymethyl chitosan complex, oxidized A mixture is prepared by dissolving magnesium alginate in deionized water, wherein the percentage of corilagin / carboxymethyl chitosan complex is 5%; then, modifier silk fibroin and dopamine-wrapped nano-hydroxyapatite are added, stirred for 10 minutes and then allowed to stand to obtain a modified corilagin / carboxymethyl chitosan complex-oxidized magnesium alginate hydrogel; wherein the mass ratio of the corilagin / carboxymethyl chitosan complex to the oxidized magnesium alginate is 1:1; and the mass ratio of the corilagin / carboxymethyl chitosan complex to the silk fibroin and dopamine-wrapped nano-hydroxyapatite is 5:2.5:2.

[0071] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0072] (1) The hydroxyapatite generated during the self-solidification of tetracalcium phosphate and calcium hydrogen phosphate has good biological activity. The released calcium and phosphate ions are conducive to the formation of a bone-like apatite layer and improve bone inductivity.

[0073] (2) The cross-linking of polymer biomaterials can provide bone cement with a three-dimensional interconnected network, which is conducive to drug loading, cell attachment, ingrowth, and subsequent osteogenic differentiation and vascular remodeling.

[0074] (3) The combination of the self-solidification of tetracalcium phosphate and calcium hydrogen phosphate and the cross-linking of polymer biomaterials shortens the setting time of bone cement and enhances the mechanical strength of bone cement.

[0075] (4) Compared with commonly used acrylic materials, polymer cross-linked self-curing drug-loaded bone cement has no obvious thermal effect during forming, which can prevent the released heat from damaging tissues and destroying the activity of doped drugs.

[0076] (5) The raw materials are widely available, the production process is simple, and it is suitable for mass production.

[0077] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.

[0078] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0079] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a polymer cross-linked self-curing drug-loaded bone cement, characterized in that: The following steps are involved: (1) grinding tetracalcium phosphate and calcium hydrogen phosphate, and passing through a sieve after grinding to obtain powders of different particle sizes; (2) mixing tetracalcium phosphate, calcium hydrogen phosphate, a cross-linking agent, and a drug uniformly to obtain bone cement powder; (3) dissolving the polymer biomaterial in purified water to obtain a polymer biomaterial aqueous solution; (4) Mix the bone cement powder and the polymer biomaterial aqueous solution evenly and allow them to solidify naturally at 37°C.

2. The method for preparing a polymer cross-linked self-curing drug-loaded bone cement according to claim 1, characterized in that: After grinding, the powder was passed through sieves of 200, 400, 600, 800, and 1000 mesh to obtain powders with particle sizes of 38-75 μm, 23-38 μm, 18-23 μm, and 13-18 μm.

3. The method for preparing a polymer cross-linked self-curing drug-loaded bone cement according to claim 1, characterized in that: The concentration of the polymer biomaterial aqueous solution is 3-10%.

4. The method for preparing a polymer cross-linked self-curing drug-loaded bone cement according to claim 1, characterized in that: The ratio of bone cement powder to polymer biomaterial aqueous solution is 0.1-1 g / mL.

5. The polymer cross-linked self-curing drug-loaded bone cement prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The bone cement powder includes, by weight: 0.73 parts of tetracalcium phosphate, 0.27 parts of calcium hydrogen phosphate, 0.002-0.01 parts of a cross-linking agent, and 0.001-0.005 parts of a drug; the ratio of the bone cement powder to the aqueous solution of the polymer biomaterial is 0.1-1 g / mL.

6. The method for preparing a polymer cross-linked self-curing drug-loaded bone cement according to claim 5, characterized in that: The cross-linking agent is genipin or 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS).

7. The method for preparing a polymer cross-linked self-curing drug-loaded bone cement according to claim 5, characterized in that: The drug is ibuprofen sodium or naringin or penicillin sodium.

8. The method for preparing a polymer cross-linked self-curing drug-loaded bone cement according to claim 5, characterized in that: The polymer biomaterial is collagen or gelatin or chitosan or silk fibroin.

Citation Information

Patent Citations

  • A multi-crosslinked injectable bone repair hydrogel material and its preparation method

    CN114984326B

  • A high-strength, fast-curing phosphate bone cement and preparation method thereof

    CN117122733B

  • Polysaccharide / calcium orthophosphate composite bone cement and preparation method thereof

    CN101496909A

  • Silk fibroin / calcium phosphate bone cement-based porous composite material and preparation method thereof

    CN102552985A

  • Injectable bioactive artificial bone material and preparation method and application thereof

    CN103736149A

Cited By

  • Implant adhesive as well as preparation method and application thereof

    CN122070942A